2017
DOI: 10.1186/s12957-017-1113-8
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of methylene blue dye as a single technique in breast cancer sentinel node biopsy: a study from Dharmais Cancer Hospital

Abstract: BackgroundAxillary lymph node dissection (ALND) has been the standard treatment of breast cancer axillary staging in Indonesia. The limited facilities of radioisotope tracer and isosulfan or patent blue dye (PBD) have been the major obstacles to perform sentinel node biopsy (SNB) in our country. We studied the application of 1% methylene blue dye (MBD) alone for SNB to overcome the problem.MethodsThis prospective study enrolled 108 patients with suspicious malignant lesions or breast cancer stages I–III. SNB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…A total of 1,559 patients in 18 studies that met the inclusion criteria were analyzed in our meta-analysis [ 27 – 44 ]. Our search strategy is presented in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1,559 patients in 18 studies that met the inclusion criteria were analyzed in our meta-analysis [ 27 – 44 ]. Our search strategy is presented in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, skin, fat and parenchymal necrosis have been reported [ 63 , 64 ]. Among the 18 studies included in present meta-analysis, Brahma reported that two patients experienced skin necrosis around the MBD injection site[ 44 ]; East reported that on patients developed skin and subcutaneous tissue necrosis around the MBD subareolar injection site[ 36 ]; and Kaklamanos reported that 3 patients suffered from skin allergic reaction[ 37 ]. No fat or parenchymal necrosis was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate identification rates (IR) as a point of success in the SLN mapping process 4 , although appropriate criteria for successful identification of a SLN is often missing. Clinical trials involving SLN mapping outline inclusion criteria for SLNs reported based on nodes that are only stained blue 2,8,23-28 , blue and non-blue nodes with dye uptake in afferent lymphatic channels 11,12,14,[29][30][31][32][33][34][35] , or do not comment on IR inclusion criteria [36][37][38] . The inconsistent or lack of standardized, objective reporting across SLN mapping trials and cases that utilize methylene blue skews accuracy and reduces comparability of results between studies.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] The optimal methylene blue dosage for SLNB remains controversial, with the most commonly used dosages being 2 and 5 ml. 13,14 Accordingly, Brahma et al, 5 who used 5 ml of methylene blue injected at the subareolar or peritumoral areas, obtained an SN detection rate of 91.7%. The present study obtained a comparable identification rate using 1.5 cm 3 of methylene blue injected at the subareolar area.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, studies that attempt to address the aforementioned limitations in performing SLNB are imperative. 4,5 New knowledge on the proposed landmark involving intercostobrachial and medial pectoral nodes as the first group of axillary lymph nodes that receive lymphatic flow from the primary tumor has allowed the utilization of a blue dye as a single tracer for detecting SNs. Lymphatic drainage from the primary tumor has been suggested to consecutively spread in a stepwise fashion to the intercostobrachial and medial pectoral nodes.…”
mentioning
confidence: 99%